Surface science techniques - Holst, Bodil; Bracco, Gianangelo (Springer Series in Surface Sciences, 2013)
The book describes the experimental techniques employed to study surfaces and interfaces. The emphasis is on the experimental method. Therefore all chapters start with an introduction of the scientific problem, the theory necessary to understand how the technique works and how to understand the results. Descriptions of real experimental setups, experimental results at different systems are given to show both the strength and the limits of the technique. In a final part the new developments and possible extensions of the techniques are presented. The included techniques provide microscopic as well as macroscopic information. They cover most of the techniques used in surface science.